Suicide literacy and stigma among undergraduate students in Pokhara, Nepal: A cross-sectional study - Dhurba Khatri; Dipendra Kumar Yadav; Shishir Paudel; Sujan Poudel; Yamuna Chhetri; Sandeepa Karki (PLoS ONE, 2025)
Background Suicide is a major global public health concern, with stigma and low suicide literacy posing significant barriers to prevention and intervention. Despite increasing suicide rates and concerns about suicidal ideation, limited studies have assessed suicide stigma and literacy among young adults in Nepal. Objective This study examines suicide literacy and stigma among undergraduate students and its associated factors. Methods A cross-sectional study was conducted among 597 randomly selected undergraduate students in Pokhara Metropolitan City, Nepal, using the Literacy of Suicide Scale (LOSS-SF) and the Stigma of Suicide Scale (SOSS-SF). Descriptive statistics, independent t-tests, and ANOVA were used to analyze socio-demographic differences. Results The mean suicide literacy score was 4.83 ± 2.07, revealing significant knowledge gaps, particularly in suicide risk factors and misconceptions. Stigma levels were high, with “pathetic” (42.4%), “immoral” (41.7%), and “stupid” (40.5%) being commonly endorsed descriptors. The average scores were 23.15 (SD ± 13.12) for SOSS-stigma, 10.10 (SD ± 3.89) for glorification, and 13.12 (SD ± 4.28) for isolation/depression. Females had higher isolation (p = 0.001) and literacy scores (p = 0.023), while males exhibited greater glorification tendencies (p < 0.001). Adults (≥20 years) had significantly higher stigma, isolation, and literacy scores than adolescents (p < 0.05). Higher isolation and literacy scores were observed among students living with family (p < 0.05) and third-year students (p < 0.01). Maternal literacy and employment were associated with higher glorification scores (p < 0.05). Conclusion These findings underscore the urgent need for suicide literacy programs and stigma-reduction initiatives in Nepalese educational institutions. Addressing misconceptions and fostering help-seeking behaviors through culturally sensitive interventions could enhance suicide prevention efforts.